Microbial chemolithotrophic oxidation of pyrite in a subsurface shale weathering environment: Geologic considerations and potential mechanisms. Issue 2 (11th October 2021) - Napieralski, Stephanie A.; Fang, Yihang; Marcon, Virginia; Forsythe, Brandon; Brantley, Susan L.; Xu, Huifang; Roden, Eric E.
Abstract: Oxidative weathering of pyrite plays an important role in the biogeochemical cycling of Fe and S in terrestrial environments. While the mechanism and occurrence of biologically accelerated pyrite oxidation under acidic conditions are well established, much less is known about microbially mediated pyrite oxidation at circumneutral pH. Recent work (Percak‐Dennett et al., 2017, Geobiology, 15, 690) has demonstrated the ability of aerobic chemolithotrophic microorganisms to accelerate pyrite oxidation at circumneutral pH and proposed two mechanistic models by which this phenomenon might occur. Here, we assess the potential relevance of aerobic microbially catalyzed circumneutral pH pyrite oxidation in relation to subsurface shale weathering at Susquehanna Shale Hills Critical Zone Observatory (SSHCZO) in Pennsylvania, USA. Specimen pyrite mixed with native shale was incubated in groundwater for 3 months at the inferred depth of in situ pyrite oxidation. The colonized materials were used as an inoculum for pyrite‐oxidizing enrichment cultures. Microbial activity accelerated the release of sulfate across all conditions. 16S rRNA gene sequencing and metagenomic analysis revealed the dominance of a putative chemolithoautotrophic sulfur‐oxidizing bacterium from the genus Thiobacillus in the enrichment cultures. Previously proposed models for aerobic microbial pyrite oxidation were assessed in terms of physical constraints, enrichment culture geochemistry, and metagenomic analysis. Although we conclude that subsurface pyrite oxidation at SSCHZO is largely abiotic, this work nonetheless yields new insight into the potential pathways by which aerobic microorganisms may accelerate pyrite oxidation at circumneutral pH. We propose a new "direct sulfur oxidation" pathway, whereby sulfhydryl‐bearing outer membrane proteins mediate oxidation of pyrite surfaces through a persulfide intermediate, analogous to previously proposed mechanisms for direct microbial oxidation of elemental sulfur. The action of this and other direct microbial pyrite oxidation pathways have major implications for controls on pyrite weathering rates in circumneutral pH sedimentary environments where pore throat sizes permit widespread access of microorganisms to pyrite surfaces.